Descriptive Epidemiology of the MOON Shoulder Instability Cohort. Issue 5 (April 2018) - Kraeutler, Matthew J.; McCarty, Eric C.; Belk, John W.; Wolf, Brian R.; Hettrich, Carolyn M.; Ortiz, Shannon F.; ,; Bravman, Jonathan T.; Baumgarten, Keith M.; Bishop, Julie Y.; Bollier, Matthew J.; Brophy, Robert H.; et al.
Background: Shoulder instability is a common diagnosis among patients undergoing shoulder surgery. Purpose: To perform a descriptive analysis of patients undergoing surgery for shoulder instability through a large multicenter consortium. Study Design: Case series; Level of evidence, 4. Methods: All patients undergoing surgery for shoulder instability who were enrolled in the MOON Shoulder Instability Study were included. Baseline demographics included age, sex, body mass index, and race. Baseline patient-reported outcomes (PROs) included the American Shoulder and Elbow Surgeons (ASES) score, Shoulder Activity Score, Western Ontario Shoulder Instability Index (WOSI), 36-Item Health Survey (RAND-36), and Single Assessment Numeric Evaluation (SANE). The preoperative physician examination included active range of motion (ROM) and strength testing. Preoperative imaging assessments with plain radiography, magnetic resonance imaging (MRI), and computed tomography were also included and analyzed. Results: Twenty-six surgeons had enrolled 863 patients (709 male, 154 female) across 10 clinical sites. The mean age for the cohort was 24 years (range, 12-63 years). Male patients represented 82% of the cohort. The primary direction of instability was anterior for both male (74%) and female (73%) patients. Football (24%) and basketball (13%) were the most common sports in which the primary shoulder injury occurred. No clinically significant differences were found in preoperative ROM between the affected and unaffected sides for any measurement taken. Preoperative MRI scans were obtained in 798 patients (92%). An anterior labral tear was the most common injury found on preoperative MRI, seen in 66% of patients, followed by a Hill-Sachs lesion in 41%. Poor PRO scores were recorded preoperatively (mean: ASES, 72.4; WOSI, 43.3; SANE, 46.6). Conclusion: The MOON Shoulder Instability Study has enrolled the largest cohort of patients undergoing shoulder stabilization to date. Anterior instability is most common among shoulder instability patients, and most patients undergoing shoulder stabilization are in their early 20s or younger. The results of this study provide important epidemiological information for patients undergoing shoulder stabilization surgery.